Institutions, Financial Development, and Small Business Survival: Evidence from European Emerging Markets - Ichiro Iwasaki; Evžen Kocenda; Yoshisada Shida (Center for Economic Studies and Ifo Institute (CESifo), 2020)
In this paper, we traced the survival status of 94,401 small businesses in 17 European emerging markets from 2007–2017 and empirically examined the determinants of their survival, focusing on institutional quality and financial development. We found that institutional quality and the level of financial development exhibit statistically significant and economically meaningful impacts on the survival probability of the SMEs being researched. The evidence holds even when we control for a set of firm-level characteristics such as ownership structure, financial performance, firm size, and age. The findings are also uniform across industries and country groups and robust beyond the difference in assumption of hazard distribution, firm size, region, and time period.
Keywords: C14; D02; D22; G33; M21; 330; small business; institutions; financial development; survival analysis; European emerging markets